(untitled) - Trefil, James S. (New York, 1998)
This book begins with the idea that the universe can be studied by observation and experiment. Encompasses physics, chemistry, astronomy, biology and earth sciences, focusing on general principles and their application to real-world situations rather than esoteric detail. Integrates the sciences rather than treating them separately. Offers students the ability to place major public issues such as the environment, energy and medical advances in a scientific context. Also examines social or philosophical issues related to science, such as the Human Genome Project and nuclear waste disposal.
Keywords: Science,Khoa học; Study and teaching (Higher),Học tập và giảng dạy; United States,Hoa Kỳ